Oral verruciform xanthoma: a case report and literature review - Marques, Yonara Maria Freire Soares [UNESP]; Andrade, Cleverton Roberto de [UNESP]; Souza, Suzana Orsini Machado de; Navarro, Cláudia Maria [UNESP] (Hindawi, 2014)
Oral verruciform xanthoma represents an uncommon entity, which affects mainly oral mucosa. This paper presents the major clinical and histological features of oral verruciform xanthoma and reports a case on the tongue. The differential diagnosis and a literature review are also provided in light of recent information.
Keywords: Verruciforme Xanthoma; Oral diagnosis; Oral medicine; Foam cell